2022
DOI: 10.35445/alishlah.v14i1.1095
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Online Learning-based Padlet during Pandemic

Abstract: This study aims to investigate the perceptions of online learning occurring during the COVID-19 pandemic. This study was applied as a case study design. The population of the research was all the second-semester students of English Language Education at one of the private universities in Riau, Indonesia. The population in this study was 173 students, while the sample was selected using random cluster sampling, amounting to 79 students. Data were collected by a questionnaire consisting of 18 questions from five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Students may explore, develop, and obtain more and better ideas by including Padlet as a digital tool in collaborative learning. These findings support previous studies by Ahmad et al, 2022, Andrews et al, 2020 They demonstrated that students responded positively to utilizing Padlets as a learning tool. This assists students with writing tasks since educational materials that can help students prepare to write are easily accessible.…”
Section: Increasing Confidencesupporting
confidence: 91%
See 1 more Smart Citation
“…Students may explore, develop, and obtain more and better ideas by including Padlet as a digital tool in collaborative learning. These findings support previous studies by Ahmad et al, 2022, Andrews et al, 2020 They demonstrated that students responded positively to utilizing Padlets as a learning tool. This assists students with writing tasks since educational materials that can help students prepare to write are easily accessible.…”
Section: Increasing Confidencesupporting
confidence: 91%
“…et al, 2020). According to Ahmad (2022) process does not only focus on what is conveyed by the teacher (Ahmad et al, 2022). The same opinion was explained by Andrew, he explained that teaching process can move from teacher as center to students centered (Andrews et al, 2020).…”
Section: Interesting To Applymentioning
confidence: 88%
“…Deni and Zainal (2018), in their study's findings, indicated that the students clearly valued the feedback they received from the teacher as it helped them to improve their writing weaknesses. These concur with the results in Meletiadou (2021) and Ahmad et al (2022) which significantly indicated that the students could produce more complex sentences and use new vocabulary since they were able to explore various texts, and their peers' work as well. Teacher written feedback enabled them to produce better and longer texts and improve various aspects of their writing, such as mechanics and grammar.…”
Section: Students' Perspective Of Teacher's Written Feedbacksupporting
confidence: 87%
“…Padlet is a learning tool that supports the students-centered teaching approach through its interactive platform. Existing body of literature (Meletiadou, 2021;Sari, 2019;Deni & Zainal, 2018) reported that the features of flexible accessibility and immediacy of teacher's written feedback helped accommodating the students' dissimilar learning styles, developed their autonomy, encouraged self-assessment and improved their writing performance (Ahmad et al, 2022;Vadia & Ciptaningrum, 2020). Deni and Zainal (2018), in their study's findings, indicated that the students clearly valued the feedback they received from the teacher as it helped them to improve their writing weaknesses.…”
Section: Students' Perspective Of Teacher's Written Feedbackmentioning
confidence: 93%
“…The Covid-19 pandemic has brought drastic changes to the education system in Indonesia and around the world. One of the big impacts on life is education, how this virus damages the existing education system as usual (Ahmad, Rubayyi, & Etfita, 2022). According to Suherdi & Mian in (Wahyuni, Satriani, & Etfita, 2021) during the COVID-19 pandemic, the change in the learning atmosphere from offline to online poses challenges and regularity in teaching.…”
Section: Introductionmentioning
confidence: 99%